MEDICAL SUPPLY SHORTAGES DURING THE COVID-19 PANDEMIC: INDONESIAS CHALLENGE AMID EXPORT LIMITATIONS - Safitri, Wahyuni; Wardah, Wardah; Iqbal, M. Putra (Universitas Syiah Kuala, 2024)
The GATT 1994 does not provide adequate international measures to address the shortage of medical supplies during emergencies, particularly pandemics. This article explores this agreement in relation to Indonesia's export restrictions during the COVID-19 pandemic. As a member state, Indonesia implemented measures to restrict the export of medical supplies, which was permitted by the WTO during this crisis. We will examine how Indonesia can invoke GATT 1994 to justify these measures. The analysis indicates that after the Indonesian government adhered to the necessary political procedures outlined by the WTO Secretariat, the implementation of export restrictions can be justified under Articles XI(2)(a), XX(b), XX(j), and XXI of the agreement. However, despite this justification, Indonesia should enhance coordination between national and international policies regarding the availability and necessity of medical supplies in relation to pandemics and other emergencies to prevent future shortages and related issues.